Pheromones and Barcoding Delimit Boundaries between Cryptic Species in the Primitive Moth Genus Eriocrania (Lepidoptera: Eriocraniidae) - Lassance JM; Svensson GP; Kozlov MV; Francke W; Lofstedt C (SPRINGER, 2022)
Animal classification is primarily based on morphological characters, even though these may not be the first to diverge during speciation. In many cases, closely related taxa are actually difficult to distinguish based on morphological characters alone, especially when there is no substantial niche separation. As a consequence, the diversity of certain groups is likely to be underestimated. Lepidoptera -moths and butterflies- represent the largest group of herbivorous insects. The extensive diversification in the group is generally assumed to have its origin in the spectacular radiation of flowering plants and the resulting abundance of ecological niches. However, speciation can also occur without strong ecological divergence. For example, reproductive isolation can evolve as the result of divergence in mate preference and the associated pheromone communication system. We combined pheromone trapping and genetic analysis to elucidate the evolutionary relationships within a complex of primitive moth species (Lepidoptera: Eriocraniidae). Mitochondrial and nuclear DNA markers provided evidence that Eriocrania semipurpurella, as currently defined by morphological characters, includes three cryptic species in Northern and Western Europe. Male moths of these cryptic species, as well as of the closely related E. sangii, exhibited relative specificity in terms of their attraction to specific ratios of two major pheromone components, (2S,6Z)-nonen-2-ol and (2R,6Z)-nonen-2-ol. Our data suggest strong assortative mating in these species in the absence of apparent niche separation, indicating that Eriocrania moths may represent an example of non-ecological speciation. Finally, our study argues in favour of combining pheromone investigations and DNA barcoding as powerful tools for identifying and delimitating species boundaries.